The incidence of oesophageal adenocarcinoma in non-dysplastic Barrett's oesophagus: a meta-analysis. Issue 7 (13th October 2011) - Desai, Tusar K; Krishnan, Kumar; Samala, Niharika; Singh, Jashanpreet; Cluley, John; Perla, Subaiah; Howden, Colin W
Abstract : Introduction: The risk of oesophageal adenocarcinoma (OAC) in non-dysplastic Barrett's oesophagus (BO) may have been overestimated. The objective was to estimate the incidence of OAC in patients with BO without dysplasia. Methods: The authors searched MEDLINE and EMBASE from 1966 to 2011 and performed a bibliographic review of previous publications, excluding abstracts, non-peer-reviewed publications and those not published in English, for prospective or retrospective studies of the incidence of OAC in patients with BO. They excluded patients with any degree of dysplasia at baseline and those without documented intestinal metaplasia. Studies were independently reviewed by two individuals. 57 of 3450 studies were included. The authors extracted information on number of patients with BO, length of follow-up, incident cases of OAC, mean age of patients, country of origin, whether prospective or retrospective, mean length of BO segments and mortality from causes other than OAC. Study quality was assessed by the Ottawa Newcastle criteria. Results: The 57 included studies comprised 11 434 patients and 58 547 patient-years of follow-up. The pooled annual incidence of OAC was 0.33% (95% CI 0.28% to 0.38%). Among 16 studies that provided appropriate information on mortality, there were 56 incident cases of OAC but 684 deaths from apparently unrelated causes. Among 16 studies that provided information on patients with short-segment BO, the annual incidence of OAC was only 0.19%. Conclusions: The incidence of OAC in non-dysplastic BO is around 1 per 300 patients per year. The incidence of OAC in short-segment BO is under 1 per 500 patients per year.